Activation of P2×7 Receptor Promotes the Invasion and Migration of Colon Cancer Cells via the STAT3 Signaling - Zhang, Wen-jun; Hu, Ce-gui; Luo, Hong-liang; Zhu, Zheng-ming (Frontiers in Cell and Developmental Biology, 2020)
The pathological mechanism of colon cancer is very complicated. Therefore, exploring the molecular basis of the pathogenesis of colon cancer and finding a new therapeutic target has become an urgent problem to be solved in the treatment of colon cancer. ATP plays an important role in regulating the progression of tumor cells. P2X7 belongs to ATP ion channel receptor, which is involved in the progression of tumors. In this study, we explored the effect and molecular mechanism of ATP-mediated P2X7 receptor on the migration and metastasis of colon cancer cells. The results showed that ATP and BzATP significantly increases the inward current and intracellular calcium concentration of LOVO and SW480 cells, while the use of antagonists (A438079 and AZD9056) could reverse the above phenomenon. We found that ATP promoted the migration and invasion of LOVO and SW480 cells and is dose-dependent on ATP concentration (100-300µM). Similarly, BzATP (10, 50, 100µM) also significantly promoted the migration and invasion of colon cancer cells in a concentration-dependent manner. While P2X7 receptor antagonists (A438079 (10µM), AZD9056 (10µM)) or P2X7 siRNA could significantly inhibit ATP-induced colon cancer cell migration and invasion. Moreover, in vivo experiments showed that ATP-induced activation of P2X7 receptor promoted the growth of tumors. Furthermore, P2X7 receptor activation down-regulated E-cadherin protein expression and up-regulated MMP-2 mRNA and concentration levels. Knocking down the expression of P2X7 receptor could significantly inhibit the increase in the expression of N-cadherin, Vimentin, Zeb1, and Snail induced by ATP. In addition, ATP time-dependently induced the activation of STAT3 via the P2X7 receptor, and the STAT3 pathway was required for the ATP-mediated invasion and migration. Our conclusion is that ATP-induced P2X7 receptor activation promotes the migration and invasion of colon cancer cells, possibly via the activation of STAT3 pathway. Therefore, the P2X7 receptor may be a potential target for the treatment of colon cancer.